2021
DOI: 10.1111/imm.13389
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐35 is a critical regulator of immunity during helminth infections associated with multiple sclerosis

Abstract: Multiple sclerosis (MS) is currently thought to arise by interactions between genetic susceptibility and environmental factors. Infections in general trigger autoimmune responses causing clinical manifestations of disease. However, as a result of regulatory T (Treg)‐ and regulatory B (Breg)‐cell induction, helminth infections tend to dampen disease activity. IL‐35, the newest member of the IL‐12 family, is an inhibitory cytokine composed of an EBI3β chain subunit, and an IL‐12p35 subunit. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
2
5
0
Order By: Relevance
“…No significant differences in IL-35 were found between single and co-infected S. mansoni patients, thereby discounting any confounding factor of co-infection for this cytokine. This general scenario aligns with the balance of the pro-and anti-inflammatory cytokines already reported in other helminth human infections [48].…”
Section: Discussionsupporting
confidence: 88%
“…No significant differences in IL-35 were found between single and co-infected S. mansoni patients, thereby discounting any confounding factor of co-infection for this cytokine. This general scenario aligns with the balance of the pro-and anti-inflammatory cytokines already reported in other helminth human infections [48].…”
Section: Discussionsupporting
confidence: 88%
“…Infection of mice with the helminth Fasciola hepatica suppresses T H 17 cells and γδT17 cells that mediate EAE through helminth induction of TGFβ 187 , type 2 cytokines and eosinophils 188 . In humans, helminth infections can reduce disease severity in patients with MS and this has been linked with IL-35 production by regulatory B cells 189 .…”
Section: Regulation Of Il-17 Activitymentioning
confidence: 99%
“…A third study reported that IL-35 was higher in MS patients as compared to healthy controls (79). In a fourth study, MS patients infected with helminths had higher levels of IL-35-producing B cells in the CSF, which correlated with reduced MRI lesions, as compared to uninfected patients (80). In vitro studies, showed that IL-35 could drive IL-35 and IL-10 production by CD19 + B cells and induce a Treg-like phenotype (80).…”
Section: The Discovery Of B Cell Negative Immune Regulationmentioning
confidence: 95%
“…In a fourth study, MS patients infected with helminths had higher levels of IL-35-producing B cells in the CSF, which correlated with reduced MRI lesions, as compared to uninfected patients (80). In vitro studies, showed that IL-35 could drive IL-35 and IL-10 production by CD19 + B cells and induce a Treg-like phenotype (80). While these studies are interesting, the lack of definitive B cell phenotyping limits impact.…”
Section: The Discovery Of B Cell Negative Immune Regulationmentioning
confidence: 99%